Green tea in medicine: a brief overview - Nayyar, Abhishek; Das, Maneesha; Deosarkar, Bharat; Deosarkar, Soniya Bharat; Karan, Abhishek; Sinha, Pallavi; Paraye, Swati (International Journal of Dental Research, 2017)
Over the past decades, focused interest in drugs obtained from medicinal plants has markedly increased. Since times immemorial, tea has traditionally been the most popular and widely consumed beverages in the world obtained from the extracts of leaves of the plant Camellia sinensis by the process of oxidation. It is the oldest non-alcoholic beverage containing caffeine. Among the varieties of tea manufactured, green tea is considered of utmost significance since it exerts antimicrobial, anti-cancer, antioxidant, anti-collagenase, anti-diabetic, anti-obesity and anti-hypertensive activities due to rich content of polyphenol, namely catechins, which prevent the pathogenesis of numerous disease processes and play a pivotal role as a scavenger of free radical generation. The present review discusses the botanical description, photo-chemical constituents and biological activity of green tea with clinical relevance in the various fields of medicine.